Beyond Engagement: How Social Media Marketing Drives Trust, Image, and Purchase Intention in Cosmetic Brands - Siringoringo, Marilyn Cynthia Margaretha (APPS Publications, 2025)
The rapid growth of internet usage significantly impacts customers’ habits, reshaping their behaviors in various ways. Correspondingly, this evolution has also transformed social media from a communication platform to a marketing tool. Today, social media marketing plays a crucial role in cultivating brand trust and shaping brand image, significantly influencing consumers’ purchase intentions. By using the theory of planned behavior, this study aims to explore the influence of social media marketing activities on purchase intentions, focusing on cosmetic brands in DKI Jakarta. This research used a quantitative approach, focuses on a sample of 177 residents of Jakarta. It aims to analyze the direct and indirect effects of social media marketing activities, brand trust, and brand image on purchase intention. The study utilizes the Smart-PLS software to evaluate the proposed hypotheses. The findings of this study reveal a notable and positive correlation between social media marketing activities, brand trust, brand image, and purchase intention. By investigating the impact of these variables on purchase intention, this research adds to the existing body of knowledge. The outcomes provide valuable insights for skincare brand management, enabling them to devise effective marketing strategies to succeed in a highly competitive market. The study suggests that managers should maximize the potential of social media marketing activities to enhance brand trust and cultivate a positive brand image, thereby promoting a favorable impact on purchase intention.